Attention and water governance: an agenda-setting perspective - Tosun, Jale; Scherer, Ulrike (Water, 2020)
The concept of agenda-setting has resulted in vibrant research in political science. The aim of this Special Issue is to advance the state of research on water governance by alluding to the possibilities for applying this particular theoretical perspective to water issues. Agenda-setting concerns how and when issues enter the public debate (discussion agenda) or are taken into account by policymakers with a view to proposing policies (decision agenda). Simply put, agenda-setting is about the process of drawing or paying attention to certain issues. Despite the intuitiveness of this concept, the underlying political and societal processes related to water governance are complex and require careful research designs in order to realize the full potential of agenda-setting research. The contributions to this Special Issue combine theoretically convincing research on agenda-setting with research on issues in water governance.
Gesehen am 05.10.2020